2020
DOI: 10.1142/s2424786320500267
|View full text |Cite
|
Sign up to set email alerts
|

A multiple parallel mediation between transformational leadership and project-based performance — A process model

Abstract: Purpose: Our purpose to write this paper is to analyze how VRIO mediates the relationship between transformational leadership and project performance by examining the direct and mediated relationships on project performance outcomes. This study combined the two dynamic concepts: project management and strategic management with the support of both literatures. Design/methodology/approach: The resource-based view is operationalized to analyze the effect of project management assets and characteristics to gain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The coefficients of up to 0.700 or above demonstrate meaningful factor loadings (Hair et al, 2017 ). Therefore, Table 2 illustrates that every factor loading is above the threshold point, although PL4 is 0.624 which is above 0.600; therefore, it can also fulfill the requirement (Hair et al, 2010 ; Ul-Haq et al, 2020 ).…”
Section: Data Analysis and Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The coefficients of up to 0.700 or above demonstrate meaningful factor loadings (Hair et al, 2017 ). Therefore, Table 2 illustrates that every factor loading is above the threshold point, although PL4 is 0.624 which is above 0.600; therefore, it can also fulfill the requirement (Hair et al, 2010 ; Ul-Haq et al, 2020 ).…”
Section: Data Analysis and Resultsmentioning
confidence: 98%
“…Several implications can be supportive toward vlogging trend, and limitations of these studies can be a roadmap for future scholars to explore the area. The authors recommend the role of the VIRO framework as mediators as suggested by Ul-Haq et al ( 2020 ) for future research.…”
Section: Discussionmentioning
confidence: 97%
“…The convergent validity of the scale was measured with factor loading for all the items. The results of factor loadings fell between the acceptable ranges from 0.4 to 0.9 (Peterson and Kim, 2013 ; Hair et al, 2017 ; Haq and Awan, 2020 ; Haq et al, 2020 ). All the items showed convergent validity by showing their respective statistics ranging from 0.6 to 0.9, hence, validating the data for convergent validity.…”
Section: Discussionmentioning
confidence: 94%
“…Through the measurement model, the variables and indicators were relied on using Cronbach's alpha and composite reliability. The cutoff value for these two statistics is 0.7 (Hair et al, 2017 ; Haq and Awan, 2020 ; Haq et al, 2020 ). All study variables meet this criterion as the alpha reliability statistic ranges from 0.85 to 0.93 and composite reliability statistic from 0.86 to 0.93; hence, meeting the criteria of reliable data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it attaches great importance to the leaders' standards of behavior and concerns for the needs of followers. Meanwhile, many reasons suggest that TL is indispensable in project organizational change [ 5 7 ]. Bass [ 8 ] argued that today's construction environment requires subordinates to perform beyond ordinary expectations, and TL can deliver.…”
Section: Introductionmentioning
confidence: 99%